Penyelesaian Konflik Kewarisan Melalui Analisa Pluralisme Hukum dan Penerapan Model Diferensiatif-Integratif dalam Harmonisasi Hukum Waris dan Adat Minangkabau - Anne Yuliana; Muhammad Ulil Albab (Muttaqien, 2026)
The Minangkabau customary inheritance system, which is matrilineal in nature, differs fundamentally from Islamic inheritance law (faraid), which prescribes fixed inheritance shares. This paradigmatic divergence often sparks tension between religious and customary norms, while also opening a space for discourse on legal pluralism in Indonesia. Consequently, this study aims to compare the Islamic and Minangkabau customary inheritance systems and formulate solutions to resolve the normative tensions between them. Employing a qualitative approach and a literature review methodology, the study conducts a comparative analysis of the inheritance principles found in both Islamic law and customary law. The findings indicate that the most realistic resolution within the context of modern Minangkabau society is the application of a “differentiative-integrative” model. This harmonization is achieved by distinguishing between categories of inherited assets: separating the status of pusaka tinggi (ancestral communal property), which is governed by customary law, from pusaka rendah (self-acquired or nuclear family property), which is managed according to Sharia rules (faraid). Overall, this research contributes a framework for resolving inheritance-related legal conflicts within the community and affirms that a legal pluralism approach can foster synergistic harmony between Islamic Sharia and local custom without necessitating the negation of one by the other.